Depleting tropical forest at a landscape scale: finding solutions for Bangladesh - Sunderland, Terry C.H.; Kibria, M.G.; Rahman, S.A.; Imtiaj, A. (2011)
Drastic deforestation is a major problem of Bangladesh which is contributing to negative downstream impacts on the environment. To address this problem various measures should be taken at different scales. The main objective of this paper is to suggest the possible steps that Bangladesh could take and reverse the trend of deforestation. An extensive literature review and interviews with government officials, professionals and NGO workers have been used to collect relevant information on the agents of deforestation in the country. Based on the information gathered, this paper presents the reasons for the extent of deforestation, and suggests some positive steps where the Government could be the main mitigating actor by implementing integrated programmes, which will also ensure mass awareness and wider impact. Local NGOs and international bodies must also formulate adequate plans to protect valuable areas of remaining forest